Social Determinant Relationship with the Pre-eclampsia Events; A Research Cross Sectional - Hasnah Hasnah; Faizal Faizal (State Islamic University of Sunan Ampel, 2019)
The main cause of maternal mortality is pre-eclampsia as many as 2 out of 5 maternal deaths. The severe complication ratio is 218/1000 and the mortality ratio of pregnant women is 198/1000. Hypertension accounted for 16 (28.1%) of 57 cases with severe complications both bleeding and abortion were 14 (24.6%). MDG’s Targets 1 to 3 in social factors contribute to the incidence of pre-eclampsia. The aim of this is to analyze the research that has three social determinan whiach are age, education and occupation associated with the incidence of pre-eclampsia. Design of this Research was a survey with a cross - sectional study approach, which was carried out from June 23 to July 28, 2018 at the Bontomanai Health Center in Jeneponto District. A sample of 45 women who experienced pre-eclampsia from January 2016 to June 2018. Data analysis with Logistic Regression is used to link dependent and independent variables. Variable proximity is seen using Odds Ratio (OR). The division of the Pre-eclampsia category is divided into two categories, namely as many as 26 people (57.8%) and mild pre-eclampsia as many as 19 people (42.2%). There are three variables in this study, age, education and occupation. Of the three variables, only age is significant while education and employment have no significance. Therefore, it can be concluded that: Subsequent research into the relationship of health status, culture with pre-eclampsia.